NEW PROCESSES OF LITERARY CREATION - Alckmar Luiz dos Santos (Revista da Anpoll, 2013)
This paper wants to discuss the status of writings (i.e., texts which are only verbal, but not digital productions) on virtual works which are not yet (or no longer) available. The aim is to investigate whether a text that presents, speculates, outlines, and designs digital creations can also be read, at least partially, as an artistic creation. In other words, would it be possible to consider as objects of art (and literary art) the writings I present here regarding two digital creations (the Sonnet and the Window wide opening machine)?